The Potential Test of Fungal Antagonist Trichoderma viride to inhibit the Growth of Pathogenic Fungi Fusarium moniliforme and Alternaria solani In-Vitro - Purwantisari, Susiana; Evendi, Agus (JURNAL SAINS DAN MATEMATIKA, 2015)
Fusarium moniliforme and Alternaria solani are two types of mold which often cause the diseases of cultivated plants. Fusarium moniliforme causes the ear rot disease on corn and the wilt disease of Solanaceae family. Whereas the pathogenic fungus Alternaria solani causes an early bright disease on the onion and potato. This aim of this study was to determine the ability of fungal antagonist Trichoderma viride in inhibiting the growth of Fusarium moniliforme and Alternaria solani in vitro. The growth inhibition ability test were conducted on dual cultures by growing the fungal antagonists with pathogenic fungi in Petri dish containing potato dextrose agar media face-to-face in a distance of 3 cm. Percentages of the growth inhibiting were observed every day in 7 days incubation. The results showed that the fungal antagonist T. viride exhibited the highest inhibition on F. moniliforme in 3 days incubation period which was 63.07 %. Yet the highest inhibition against A. solani was in 2 days incubation period which was 57.35 %. T. viride growth continued to increase since the first day until the seventh day incubation period but contrarily the growth of both pathogenic fungi underwent inhibition. This suggested that T. viride was potential as a biological control agent of F. moniliforme and A. solani growth and have a potency as an active bio fungicide ingredient. Keywords: Dual culture; percentage inhibiting; Trichoderma viride; Alternaria solani; Fusarium moniliforme